Acute Kidney Injury Following Transurethral Resection of the Prostate in a Patient with Hepatitis C: A Case Report - Fazri, Akhmad Miftahudin; Tobing, Edwin; Tansol, Christiano (Journal of Neonatal Surgery, 2025)
Introduction: Transurethral resection of the prostate (TURP) is a widely performed urologic procedure. Although postoperative acute kidney injury (AKI) is uncommon, it may occur through various mechanisms. Case Presentation: We report details an 81-year-old male with chronic HCV who presented with lower urinary tract symptoms and underwent an uncomplicated monopolar TURP. Despite the absence of chronic kidney disease and intraoperative complications, the patient developed AKI two days post-surgery, characterized by confusion and elevated creatinine levels (0.94 to 5.53 mg/dL). He required multiple hemodialysis sessions for metabolic derangements. The interplay between HCV-related renal pathologies and surgical stress likely contributed to the AKI, highlighting the vulnerabilities faced by elderly patients with underlying liver conditions. Early nephrology consultation and renal monitoring are critical for improving prognosis in individuals experiencing postoperative AKI linked to chronic hepatitis C. Conclusion: This case underscores the necessity for comprehensive preoperative assessments, vigilant intraoperative monitoring, and proactive postoperative care to mitigate AKI risks in this high-risk population. Given the increasing incidence of surgical interventions in geriatric patients with HCV, further research is essential to establish effective management protocols and enhance patient outcomes following TURP.